The Effectiveness of Macrophage Hydrolyzed VCO Cream in Healing Second Degree Burns in Wistar Rats - Fahmi Syarif; Najatullah Najatullah (RSUP Dr. Kariadi, 2024)
Background: Burns are a global public health issue, with many studies on topical medications that are effective in second-degree burns. Hydrolyzed VCO (hVCO) contains lauric acid, polyferol and alpha tocopherol which are beneficial in wound healing. This study was conducted to determine the effectiveness of hVCO cream macrophage formation for second degree burn wound healing in Wistar rats. Methods: A parallel group study was conducted on thirty wistar rats randomly divided into six groups induced second degree burns. Basic cream was applied to two control groups on the 6th and 12th day, 70% hVCO was applied to two groups on the 6th and 12th day, and 100% hVCO was applied to two groups on the 6th and 12th day. Histopathological examination of macrophage formation was conducted in each treatment. Result: The groups with hydrolyzed VCO cream on day 12 (p=0,089) had higher macrophage formation than the same hVCO group on day 6 (p=0,354). The macrophage count of hVCO in each group showed an increase. Conclusion: 100% hVCO is effective in accelerating second degree burn wound healing in terms of macrophage count.